Applying data mining classification techniques for employee’s performance prediction - Jantan, Hamidah; Puteh, Mazidah; Hamdan, Abdul Razak; Ali Othman, Zulaiha (2010)
The valuable knowledge can be discovered through data mining process.In data mining, classification is one of the major tasks to impart knowledge from huge amount of data. This technique is widely used in various fields, but it has not attracted much attention in Human Resource Management (HRM). This article presents a study on the implementation of data mining approach for employee development regarding to their future performance.By using this approach, the performance patterns can be discovered from the existing database and will be used for future performance prediction in their career development. In the experimental phase, we have used selected classification techniques to propose the appropriate technique for the dataset. An experiment is carried out to demonstrate the feasibility of the suggested classification techniques using employee’s performance data. Thus, the experiment results, we suggest the potential classification techniques and the possible prediction model for employee’s performance forecasting.